1997
DOI: 10.1007/bf02765827
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor alpha (TGF-α) gene in mouse embryonic development

Abstract: Purpose: The expression of genest for TGF-ct, epidermal growth factor (EGF), and the EGF receptor (EGFR) in mouse blastocysts was evaluated by the reverse transcription-polymerase chain reaction (RT-PCR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The EGF ligand is involved in the formation of hatched blastocysts [12], but its receptor remains at low levels until the four-cell stage [13]. Although TGF␣ reduces the incidence of apoptosis in mouse blastocysts [14], it is not detected before the four-cell stage [15]. Thus, receptor PTKs for peptide growth factors do not seem to be involved in the regulation of development before the four-cell stage.…”
Section: Introductionmentioning
confidence: 94%
“…The EGF ligand is involved in the formation of hatched blastocysts [12], but its receptor remains at low levels until the four-cell stage [13]. Although TGF␣ reduces the incidence of apoptosis in mouse blastocysts [14], it is not detected before the four-cell stage [15]. Thus, receptor PTKs for peptide growth factors do not seem to be involved in the regulation of development before the four-cell stage.…”
Section: Introductionmentioning
confidence: 94%
“…TGF-α has been demonstrated to stimulate DNA and protein synthesis in blastocysts as well asincrease the rate of blastocoel expansion. Administration of TGF-α antisense ODN significantly reduces the rate of blastocoel expansion 28. Rate of blastocoel expansion is shown to increase in the presence of acrogranin.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have revealed transcripts for this growth factor in embryos of several species, including human (Klonisch et al, 2001), bovine (Chia et al, 1995;Kobayashi et al, 1994), porcine (Singh et al, 1993) and mouse (Das et al, 1991;Harada et al, 1997). EGF mRNA is rapidly down-regulated in mouse embryos (Das et al, 1991;Moller et al, 2001), suggesting that although detection in zygotes is due to internalization of maternal EGF during oogenesis, IVF-derived and cloned embryos are capable of expressing EGF independent of maternal influence (Kidder, 1992;Wiley et al, 1992).…”
Section: Figmentioning
confidence: 97%